Energy-Efficient Nitrification and Microbial Community in a Completely Stirred Membrane Biofilm Reactor - Taskan, Ergin; Hanay, Ozge; Hasar, Halil (Mary Ann Liebert, Inc, 2015)
Oxygen-based membrane biofilm reactor, in which oxygen diffuses from the inside of membrane fibers to the biofilm located on the outer surface of each fiber, accomplished effective nitrification because the gas substrate under even low pressures was completely utilized as an electron acceptor. Oxygen flux reached 19.7 g O-2/m(2)-day at an ammonium loading of 11.15 g N/m(2)-day and the system tolerated the ammonium loading of 4.4 g N/m(2)-day at an oxygen pressure as low as 0.034 atm and hydraulic retention time (HRT) of 2.5 h by achieving complete nitrification. To better understand the microbial composition of biofilm, polymerase chain reaction-denaturing gradient gel electrophoresis analysis was applied. Molecular technique based on 16S rRNA gene sequences indicated that the biofilm consortium included Nitrosospira sp. and Nitrosopumilus maritimus, which have played an important role in efficient nitrification.
Keywords: membrane biofilm reactor; nitrification; microbial community